Surfactant modified ZnO–Bi2O3 nanocomposite for degradation of lambda- cyhalothrin pesticide in visible light: A study of reaction kinetics and intermediates. (15th September 2019) - Premalatha, N.; Rose Miranda, Lima
Abstract: Coupling of semiconductor photocatalyst attracted more attention in the area of heterogeneous photocatalytic process. Herein we developed a low-cost visible light responsive coupled ZnO–Bi2 O3 semiconductor with a molar ratio of 1:4, 1:2, and 3:4 by facile one-step hydrothermal method using a surfactant. The influences of Bi2 O3 content on coupled catalyst were investigated. The synthesized catalysts were characterized by X-Ray diffraction (XRD), scanning electron microscope (SEM), Fourier transform infrared spectrum (FT-IR), UV–Vis diffuse reflectance (UV-DRS). Photocatalytic performance of ZnO–Bi2 O3 was investigated using Lambda-Cyhalothrin (L-CHT), a pyrethroid pesticide that is harmful to human beings and animals under visible light irradiation. Kinetic study of the degradation of L-CHT reveals that there is a shift in the reaction order from first-order to second-order. The photocatalytic degradation of L-CHT using ZnO–Bi2 O3 is found to be more efficient since the separation of photogenerated holes and electrons are improved by coupling of ZnO with Bi2 O3 . When compared to bare ZnO the degradation percentage of 85.7% was achieved within 120 min of the photocatalytic process using the catalyst dosage of 1.2 gm/L in 50 mg/L of L-CHT solution with formation of Phthalic acid, butyl 2-ethyl butyl ester and Diethyl phthalate as intermediates. No other hazardous intermediates are formed and a scheme for photodegradation pathway was proposed. Graphical abstract: Image 1 Highlights: Triton-X as a surfactant during hydrothermal preparation of ZnO–Bi2 O3 . Highly efficient ZnO–Bi2 O3 active under visible light for degradation of Lambda-Cyhalothrin. A study of a shift in the reaction order from first-order to second-order for the higher concentration of Lambda-cyhalothrin. Formation of Phthalic acid, butyl 2-ethyl butyl ester as reaction intermediate at 50 mg/L concentration of pesticide. Further degradation to Diethyl Phthalate as the concentration decreases to 20 mg/L with formation of no other toxic intermediates.